ENGLISH TEACHERS’ PERCEPTIONS TOWARD TEACHING MEDIA IN SENIOR HIGH SCHOOL NO.7 BENGKULU CITY - Fadel Havip (Fakultas Keguruan dan Ilmu Pendidikan, 2021)
The objective of this research was to find out English Teachers’ Perceptions of English Language Teaching Media. The research design of this research used descriptive qualitative method. The data collected used the questionnaire adopted from Soko (2017) about ELT media based on Rao (2014) theory. The result of this research is: first. the teachers have very good or positive perception about view and understanding of ELT Media in teaching English. It means the teachers believe that English language teaching will be done effectively if they are assisted by other supporting system including media.Second, the teachers have bad or negative perception about action of ELT Media It means, in implementation media in teaching the teachers only rely on certain media especially in enhancing the students’ language comprehension such as listening, speaking, reading and writing. Based on the result above, the researcher give suggestion for teacher, be more creative and innovative in choosing teaching media to improve the students ability, so that teachers do not use the same media every time they teach doing, it is expected that the chance for their manuscript to be accepted for publication in an international journal is higher Key Words : Teaching, Teaching, and Learning Process, Media